Quantitative Evaluation of the Community Research Fellows Training Program - Lucy eD'Agostino McGowan; Jewel eStafford; Vetta Lynn Thompson; Bethany eJohnson; Melody S. Goodman (Frontiers Media S.A., 2015)
Context: The Community Research Fellows Training (CRFT) program is a community-based participatory research (CBPR) initiative for the St. Louis area. This fifteen week program, based on a Master in Public Health curriculum, was implemented by the Division of Public Health Sciences at Washington University School of Medicine in partnership with the Siteman Cancer Center. Objectives: We measure the knowledge gained by participants and evaluate participant and faculty satisfaction of the CRFT program both in terms of meeting learning objectives and actively engaging the community in the research process.Participants: We conducted analyses on 44 community members who participated in the CRFT program and completed the baseline and follow-up knowledge assessments.Main Outcome Measures: Knowledge gain is measured by a baseline and follow-up assessment given at the first and final session. Additionally, pre- and post-tests are given after the first 12 sessions. To measure satisfaction, program evaluations are completed by both the participants and faculty after each topic. Mid-way through the program, a mid-term assessment was administered to assess the program's community engagement. We analyzed the results from the assessments, pre- and post-tests, and evaluations.Results: The CRFT participants' knowledge increased at follow-up as compared with baseline on average by a 16.5 point difference (p<0.0001). Post-test scores were higher than pre-test scores for 11 of the 12 sessions. Both participants and faculty enjoyed the training and rated all session well.Conclusions: The CRFT program was successful in increasing community knowledge, in participant satisfaction, and in faculty satisfaction. This success has enhanced the infrastructure for CBPR as well as led to CBPR pilot projects that address health disparities in the St. Louis Greater Metropolitan Area.